Evaluation of the effectiveness of mobile applications for learning and sharing of Islamic knowledge : a case study of the International Islamic University Malaysia - Hosseini, Seyed Ebrahim (Kulliyyah of Information and Communication Technology, Internationai Islamic University Malaysia, 2015)
Knowledge refers to advanced information achieved through combining data, information, facts, skills, multiple experiences and formal educations. In Islam, knowledge is considered to be very important and has been identified as worship. The text of Quran is supplied with verse to invite everyman to utilize his intellect, to ponder, think and to know the goal of human life (i.e. to discover the truth, which is none other than worshipping God and his oneness). The Hadith literature also emphasizes the importance of knowledge. Islamic knowledge can be learnt and shared through different ways such as: going to Islamic events or talks, and reading Quran and reading Islamic resources (i.e. books and magazines). In the past, the spread of religious knowledge throughout the Muslims world was limited by a lack of communication tools However, there is a recent trend in Learning and sharing Islamic knowledge that be done through mobile applications. Therefore, this research is aimed to measure the perceptions of using of mobile applications in learning and sharing of Islamic knowledge among IIUM's students. The research questions of this study are: (1) Do mobile applications influence the learning of Islamic knowledge among IIUM University students? (2) Do mobile applications affect the sharing of Islamic knowledge among IIUM University students? (3) Are mobile applications effective tools in learning and sharing Islamic knowledge? Based on the results of analysis, mobile applications are a significant predictor of learning knowledge. In addition, the results showed that mobile applications have a significant positive effect in sharing knowledge among university students. The results also showed that mobile applications are positively effective tools in learning and sharing Islamic knowledge.